An Efficient Image Forgery Detection Method with Dempster Shefer’s Theory for Detecting Jpeg Anti-Forensics (International Journal of Engineering and Computer Science, 2015)
-With rapid development of high-quality cameras and powerful photo-editing tools significantly reduces thedifficulty to make visually plausible fake images. The JPEG format is widely used as one of the most popular lossy imagecompression formats is used by various advanced digital cameras and image editor and processing software tools. Earlier workidentified traces of the image JPEG compression history or JPEG anti-forensic processing with reasonable loss of imagequality. This aims at removing from a given image the footprints in both the spatial and frequency domain left by JPEGcompression. However, efficient forensic Undetectability not obtained. To deal with this problem the present work proposesdifferent forgery detection algorithm such as Ststic image Format Analysis algorithm, lossy compression technique Effect andPlace/Transfer Forgery. The result of this algorithm is combined by using Dempster-Shafer combiner which is based on theDempster-Shafer theory as a framework within which the results of different tools are considered and taken decision.Experimental result of proposed system efficiently detects the Undetectability forgeries when and provides better result whencompare with earlier methods.